Emerging energy and environmental applications of vertically-oriented graphenes1. (21st April 2015) - Bo, Zheng; Mao, Shun; Jun Han, Zhao; Cen, Kefa; Chen, Junhong; Ostrikov, Kostya (Ken)
<x xml:space="preserve">Abstract</x> This tutorial review summarizes plasma synthesis of vertically-oriented graphenes, their growth mechanisms and unique properties for energy and environmental applications.